COVID-19 Is Not the Flu: Four Graphs From Four Countries - Stojanovic, Jovana; Boucher, Vincent G.; Boyle, Jacqueline; Enticott, Joanne; Lavoie, Kim L.; Bacon, Simon L. (Frontiers in Public Health, 2021)
Background: COVID-19 has caused a global public health emergency. Government mitigation strategies included a series of behaviour-based prevention policies that had a likely impact on the spread of other contagious respiratory illnesses, such as seasonal influenza. Our aim was to explore how 2019-2020 influenza tracked onto COVID-19 pandemic and its mitigation methods. Materials and methods: We linked the WHO FluNet database and COVID-19 confirmed cases (Johns Hopkins University) for four countries across the northern (Canada, United States) and southern hemispheres (Australia, Brazil) for the period 2016-2020. Graphical presentations of longitudinal data were provided. Results: There was a notable reduction in influenza cases for the 2019-2020 season. Northern hemisphere countries experienced a quicker ending to the 2019-2020 seasonal influenza cases (shortened by 4-7 weeks) and virtually no 2020 fall influenza season. Countries from the southern hemisphere experienced drastically low levels of seasonal influenza, with consistent trends that were approaching zero cases after the introduction of COVID-19 measures. Conclusions: It is likely that the COVID-19 mitigation measures played a notable role in the marked decrease in influenza, with little to no influenza activity in both the northern and southern hemispheres. In spite of this reduction in influenza cases, there was still community spread of COVID-19, highlighting the contagiousness of SARS-CoV-2 compared to influenza. These results, together with the higher mortality rate from SARS-CoV-2 compared to influenza, highlight that COVID-19 is a far greater health threat than influenza.